PENGUATAN KOMPETENSI DAN SPIRITUAL PENDIDIK PAUD YAYASAN KAIROS TANAH PAPUA SORONG, PAPUA BARAT DAYA - Indriana Purba, Rosma; Bunda, Dince; Praja Kusumah, Indra; Appulembang, Oce; Sari, Ganda (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Teachers are not merely transmitters of knowledge but also serve as character builders and spiritual mentors. This community service program was designed to equip early childhood educators from the Kairos Foundation in Sorong, Southwest Papua, with a comprehensive understanding of the competencies required of educators, the characteristics of learners from a Christian worldview, and the challenges faced by educators in the 21st century. These challenges were explored through the lens of 21st-century skills and with reference to the Regulation of the Indonesian Minister of Education and Culture No. 137 of 2014. Through a reflective and contextual approach involving discussions and assignments, the online training—attended by sixteen teachers—resulted in improved educator understanding, as evidenced by their ability to clearly and critically explain the four key aspects covered. This training not only enhanced the participants’ conceptual understanding but also affirmed their identity and strategic role as educators in shaping a generation that is intellectually capable and deeply rooted in Christian values. Ultimately, the training serves as a practical guide for meaningful and transformative teaching.